MATURATION AND SPAWNING IN POLYNEMUS HEPTADACTYLUS CUV. AND VAL. - Kagwade, P V (Indian Journal of Fisheries, 2011)
The maturity cycle of Pclynemus heptadactyius has been described. The ripe ova measure 0.64 -1.04 mm in diameter, and each ovum contains one to many oil globules. Size at first maturity is 133 mm in female and 128 mm in males, when the fish has completed its second year of life. Females dominated in number in almost all length groups. Males were totally absent in length groups above 203 mm. Spawning is prolonged, and the release of ova is in batches. Individual fish spawns twice with an interval of six months; but with slight diversities in their individual spawning periods, the spawning of the species appears to be throughout the year. All the maturity stages are obtained all through the year. There are two peak spawning seasons, March-June and August-November, and two recruitments every year. The spawning intensity seems greater in ofTshore waters. The fish appears to spend the juvenile stages in inshore waters